2021
DOI: 10.3389/fnut.2020.608623
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Fermented High-Fiber Rye Diet on Helicobacter pylori and Cardio-Metabolic Risk Factors: A Randomized Controlled Trial Among Helicobacter pylori-Positive Chinese Adults

Abstract: Background: High dietary fiber intake has been associated with reduced risk of Helicobacter pylori infection and co-morbidities such as gastric cancer but also with reduced risk of cardiovascular disease. It has been suggested that fermented rye could affect Helicobacter pylori bacterial load and that high- fiber rye may be superior to wheat for improvement of several cardiometabolic risk factors, but few long-term interventions with high fiber rye foods have been conducted.Objective: To examine the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
(108 reference statements)
1
9
0
Order By: Relevance
“…This is line with finding from other studies showing reduced concentration of inflammatory markers following interventions with high cereal fiber intake, including whole grain rye [20,49e51]. However, low grade inflammation is associated with overweight and weight loss and the larger weight loss in the rye group may partially explain the reduction in inflammation [52], but other studies where subjects remained weight stable showed positive effects of rye, indicating and independent effect of rye [20,49]. LDL cholesterol increased in the wheat group, indicating an adverse effect of the wheat products.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is line with finding from other studies showing reduced concentration of inflammatory markers following interventions with high cereal fiber intake, including whole grain rye [20,49e51]. However, low grade inflammation is associated with overweight and weight loss and the larger weight loss in the rye group may partially explain the reduction in inflammation [52], but other studies where subjects remained weight stable showed positive effects of rye, indicating and independent effect of rye [20,49]. LDL cholesterol increased in the wheat group, indicating an adverse effect of the wheat products.…”
Section: Discussionsupporting
confidence: 90%
“…LDL cholesterol increased in the wheat group, indicating an adverse effect of the wheat products. Generally, rye, and whole grain in general, have been shown to have a positive influence on LDL cholesterol [19,20] and weight loss is also associated with reductions in LDL cholesterol [53]. Based on this, we expected a difference between the groups to arise from a reduction in LDL cholesterol in one/both intervention groups, rather than an increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we were not able to evaluate lifestyle and especially diet in our population; in a Chinese study (n = 3014), it was revealed that a rich-in-salt diet is linked with Hp-I, whereas a “vegetable and grain” dietary pattern is associated with a diminished risk of Hp-I [ 92 ]. Additionally, in a recent study focusing on the same ethnic population ( n = 182), it was demonstrated that Hp -I (+) individuals following a high-fiber rye diet had a lower high sensitive C-reactive protein, as well as low-density lipoprotein cholesterol, compared to a control group following a refined-wheat diet [ 93 ]. A third large scale (n = 10,407) Chinese study deduced that a carbohydrates/sweets-based diet was positively associated with the Hp-I, whereas a high intake of animal offal, animal blood, fish, seafood, and poultry diet was inversely associated with Hp-I prevalence [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rye bran was fermented with L. plantarum DSMZ 13890 by mixing the bran with autoclaved tap water (1:5 w/w) and incubating at 37 °C for 24 h, as described in more detail by Xue et al. [ 25 ] Samples were taken at the beginning of the fermentation, at 6 h, and at 24 h (end of the fermentation). The fermented rye bran, with a final concentration of L. plantarum DSMZ 13890 estimated at 10 9 cfu mL −1 , was then dried and incorporated into a tailor‐made rye crackerbread (WG rye with fermented rye bran).…”
Section: Methodsmentioning
confidence: 99%